PENGARUH IKLIM SEKOLAH DAN DISIPLIN TERHADAP KINERJA GURU MEDIASI MOTIVASI - Irianti, Endang (Students Journal of Economic and Management, 2012)
Purpose of this research is to test and description of influence: 1) school climate to motivation of job, 2) job discipline to motivation of job, 3) motivation of job to teacher performance, 4) school climate to teacher performance, and 5) job discipline to teacher performance.This research executed in TK Wilayah Kecamatan Tambakromo Kabupaten Pati, teacher sample TK 101 teacher by using nonprobability sampling. Collecting propagates questionnaire, applies scale model equate Likert with modification 7 scale. Analytical technique applied is descriptive, linear partial correlation and regression at level significance 5%.Result of descriptive analysis indicates that responder comments about statement of questionnaire propagated about teacher performance, school climate, teacher job discipline and motivation of teacher job average of responder answers